1972
DOI: 10.1002/j.1551-8833.1972.tb02630.x
|View full text |Cite
|
Sign up to set email alerts
|

Disposal of Alum Sludges

Abstract: Now that environmental protection is receiving increasing attention, it is becoming imminently necessary to find alternative methods for disposing of water‐treatment‐plant sludge. The author briefly reviews the technology of the field and then analyzes the significance of laboratory tests conducted to determine optimum disposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1973
1973
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…3. A long-range sludge-sampling pro gram was initiated at the four stations on Feb. 6,1973. At sampling station 1 two sludge samples were secured: sample A at the sludge surface, and sample B at 1.5 ft below the surface.…”
Section: Field Monitoring Of Sludge Dewaterabilitymentioning
confidence: 99%
“…3. A long-range sludge-sampling pro gram was initiated at the four stations on Feb. 6,1973. At sampling station 1 two sludge samples were secured: sample A at the sludge surface, and sample B at 1.5 ft below the surface.…”
Section: Field Monitoring Of Sludge Dewaterabilitymentioning
confidence: 99%
“…It has been reported that lime-soften ing sludges high in magnesium content are more difficult to dewater by vacuum filtration than sludges low in magnesium content. [2][3][4][5][6][7][8][9][10][11][12] To investigate the effect of magnesium hardness on specific resist ance, two stock solutions of calcium and magnesium hardness were prepared: 92 mg/1 calcium as CaCO3 and 48 mg/1 mag nesium as CaCO3; and 136 mg/1 calcium as CaCO3 and 52 mg/1 magnesium as CaC03. Alkalinity was held constant throughout at 308 mg/1 as CaCO3 .…”
Section: Effect Of Magnesium Hardness On Specific Resistancementioning
confidence: 99%
“…In addition, alum has been proven as one of an effective conventional flocculants since ancient times, its application in water treatment generate secondary by-products that are non-Newtonian and gelatinous that complicate sludge disposal by waste treatment plants (Nadella et al 2020;Albrecht 1972). While in the case of non-nanobiopolymer flocculants, even though they are normally considered as not toxic and environmentally friendly however there are limitations regarding their short shelf life and moderate operational performance.…”
Section: Introductionmentioning
confidence: 99%